SPOSOBY NOMINACJI OSOB W ZAPISACH KSIG SDOWYCH Z TERENU STAROSTWA HRUBIESZOWSKIEGO W XVII WIEKU - Kojder, Marcin; Kojder, M. (My University, 2010)
У статті проаналізовані імена осіб із судових актів XVII століття з території Грубешівського староства. Встановлено, що більшість найменувань осіб складалася з двох елементів, відзначене вживання і неповних імен. Виявлені і більш складні найменування -з трьох або чотирьох елементів. The article presents an analysis of strategies adopted for naming people in court registers of Starostwo Hrubieszowskie (Hrubieszow District) in the XVII century. In the XVII century, the majority of names in Hrubieszow District consisted of two elements, nevertheless, a small number of single-element names were also noted. Moreover, some examples of more complex names - consisting of three or four elements - were also found.
Keywords: антропонім; власне ім'я; прізвище; польсько-українське пограниччя; anthroponomy; proper name; personal name; surname; polish-ukrainian borderland